High resolution stereolithography fabrication of perfusable scaffolds to enable long-term meso-scale hepatic culture for disease modeling. (21st September 2021) - Sphabmixay, Pierre; Raredon, Micha Sam Brickman; Wang, Alex J-S; Lee, Howon; Hammond, Paula T; Fang, Nicholas X; Griffith, Linda G
Abstract: Microphysiological systems (MPS), comprising human cell cultured in formats that capture features of the three-dimensional (3D) microenvironments of native human organs under microperfusion, are promising tools for biomedical research. Here we report the development of a mesoscale physiological system (MePS) enabling the long-term 3D perfused culture of primary human hepatocytes at scales of over 10 6 cells per MPS. A central feature of the MePS, which employs a commercially-available multiwell bioreactor for perfusion, is a novel scaffold comprising a dense network of nano- and micro-porous polymer channels, designed to provide appropriate convective and diffusive mass transfer of oxygen and other nutrients while maintaining physiological values of shear stress. The scaffold design is realized by a high resolution stereolithography fabrication process employing a novel resin. This new culture system sustains mesoscopic hepatic tissue-like cultures with greater hepatic functionality (assessed by albumin and urea synthesis, and CYP3A4 activity) and lower inflammation markers compared to comparable cultures on the commercial polystyrene scaffold. To illustrate applications to disease modeling, we established an insulin-resistant phenotype by exposing liver cells to hyperglycemic and hyperinsulinemic media. Future applications of the MePS include the co-culture of hepatocytes with resident immune cells and the integration with multiple organs to model complex liver-associated diseases